2021
DOI: 10.3390/insects12040351
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR-14 Regulates Egg-Laying by Targeting EcR in Honeybees (Apis mellifera)

Abstract: Honeybees (Apis mellifera) are important pollinators and are commonly used for honey production. The oviposition behavior in honeybees is complex and errors in oviposition could affect the development of the bee colony. Recent studies reported that RNA–RNA cross-talk played a critical role in several biological processes, including reproduction. Ecdysone receptor (EcR) and miR-14 were previously reported to play important roles in egg-laying. Moreover, EcR was predicted to be the target gene of miR-14 and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…We discovered that the miR-34 and miR-14 in the EVs might modulate the Eip74EF and EcR respectively during the various molt stages. Previous studies have shown that miR-14 directly targets the mRNA of EcR (Chen and Fu, 2021). miR-34 is highly conserved in insects and has been shown to interact with the 3' UTR of the Eip74EF mRNA through the predicted binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that the miR-34 and miR-14 in the EVs might modulate the Eip74EF and EcR respectively during the various molt stages. Previous studies have shown that miR-14 directly targets the mRNA of EcR (Chen and Fu, 2021). miR-34 is highly conserved in insects and has been shown to interact with the 3' UTR of the Eip74EF mRNA through the predicted binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the lack of DA significantly increased the concentration of JH (Figure S5A) and inhibited expression of JH esterase (Figure S5B). Moreover, some studies have shown that miR‐14 targets ecdysone receptor ( EcR ) to regulate ecdysone signaling during growth and development, affecting insect development time, such as egg laying and other processes 61–63 . In H. armigera , it has been reported that miR‐14 positively regulates the HaEcR , 64 suggesting that miR‐14 is a common regulator of ecdysone and DA.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 153 known miRNAs obtained in the present study, ame-miR-276-3p, ame-miR-375-3p, ame-miR-14-3p, ame-miR-275-3p, and ame-miR-3477-5p were the top five most abundant miRNAs that commonly existed in NB, FB, and NEB libraries ( Table 2 ). A recent study demonstrated that ame-miR-14 was enriched in the queen ovary and played an important role in regulating egg-laying via modulating ecdysone receptor in honeybee queens [ 26 ]. The miRNA ame-mir-276 is highly expressed in the small-type Kenyon cells of the mushroom bodies and is involved with the development of related neural function in honeybees [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA) is a class of small (18–24 nt), single-strand, and endogenous ncRNA that plays important roles in the post-transcriptional regulation of target gene expression [ 16 , 17 ] related to various biological processes, such as tissue development [ 18 ]. Previous studies on honeybee miRNAs revealed their key roles in mediating diverse physiological processes, such as caste differentiation [ 19 , 20 ], division of labor [ 21 , 22 ], memory formation [ 23 , 24 ], queen reproductive performance [ 25 , 26 ], immune defense [ 27 , 28 ], and embryonic and midgut development [ 29 , 30 ]. However, little is known about whether/how miRNAs regulate the HPGs development in worker bees.…”
Section: Introductionmentioning
confidence: 99%